Światowy rynek miedzi w latach 2003-2004 - stan obecny oraz perspektywy rozwoju - Szeląg, Tomasz (The World Copper Market in 2003-2004 - Current Situation and Future Perspectives, 2005)
The fundamental situation on the world copper market has changed recently. After six years of permanent surplus of the metal (1997-2002), in 2003 one deals with a deficit, caused by a number of factors', simultaneous decline of global copper production and an increase of global copper consumption, a huge activity of investment funds, depretiation of US dollar against euro and last but not least, an unexpected supply shortages (force majeures, technical problems or strikes). As a result, copper prices have reached an eight-year historical levels. The main purpose of this article is to present different views on copper market of people who work for banks, financial institutions and independent analytical companies that deal with the world copper market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 373-384